The Influence of Turnover Factors Toward Employees’ Intention to Stay: A Case Study in Indonesian Islamic Universities - Malik, Nazaruddin (Department Industrial Engineering, University of Muhammadiyah Malang, 2020)
This study analyzed several employee turnover factors, such as satisfaction, organizational commitment, and religiosity, to predict the employees’ intention to stay. Very few studies in the Muslim context have explored such a corporate attitude from the viewpoint of job satisfaction and organizational commitment. This study employed a quantitative and descriptive research design. A survey was used to analyze the correlation between some predictors of the employees’ intention to stay. In particular, it attempted to show that religiosity affected both job satisfaction and organizational commitment either directly or indirectly. The data were obtained from 150 employees in some Islamic universities in Malang. The findings revealed that (1) job satisfaction was influenced by religious beliefs. (2) job satisfaction significantly affected the employees' commitment. (3) religiosity gave an indirect positive impact to the corporate commitment through job satisfaction, and 4) religiosity was positively related to the employees' intention to stay. Regarding this, the employees who keep the religious belief in the workplace are encouraged to bring themselves to perform excellently.